Assessment Of Vaccine Wastage in A Tertiary Care Centre of District Rohtak, Haryana - Vikas Gupta; Debjyoti Mohapatra; Vijay Kumar (Medsci Publications, 2015)
Background: India released its first national vaccine policy in 2011. India is facing such less coverage and one of the rationales behind it is mismanagement of vaccine logistics. Vaccine wastage is de- fined as loss by use, decay, erosion or leakage or through wasteful- ness. Methods: This was a record based descriptive study carried out at immunization clinic of Pt. B.D Sharma PGIMS, Rohtak. The infor- mation of vaccine vials used at immunization clinic and children (up to age of 16 years) vaccinated were retrieved from the immun- ization registers for the reference period of 1st October 2013 and 31st December 2013. Results: Among individual vaccines, wastage factor and wastage rate was highest for BCG and was lowest for pentavalent vaccine. Differences in wastage rates for different vial size were statistically significant. Wastage factor and wastage rate were higher in lyoph- ilized vaccines (2.75) and (63.76%) compared to that of liquid vac- cines i.e. (1.35) and (26.36%). Conclusion: Vaccine wastage can be obtained by actual monitoring of the immunization clinic. This can save significant funds for an immunization programme if wastage can be reduced without af- fecting the coverage.